Dying of Sal - Boyce, J. S.; Bakshi, B. K. (Indian Forester, 1959)
Dying of sal is occurring in many localities, particularly on poor sites, throughout its range in India. Though no one cause could be ascribed, it is believed that generally dying is due to deteriorating site conditions, probably the most important single factor being lessened amount of soil moisture. A fungus Hypoxylon mediterraneum is constantly associated with dead and dying sal. The fungus is believed to be pathogenic following the loss of vigour in sal and hastens the death of trees or prevents their recovery. It is believed that improvement of site by proper silviculture will restore the health of the stands.